The Influence Of Servant Leadership And Auditor Competence On The Improvement Of Internal Audit Effectiveness With The Creation Of Risk Culture As An Intervening Variable In The Main Inspectorate Of BRIN - Bona Ernest; Sunu Widianto; Arief Hadianto (Green Publisher Indonesia, 2024)
The National Research and Innovation Agency (BRIN), established in 2021, integrates various research institutions in Indonesia to focus on research and innovation without regulatory duties. This study investigates the impact of servant leadership, auditor competence, and risk culture on the effectiveness of internal audits at BRIN, utilizing a quantitative method with data collected via questionnaires from BRIN's Main Inspectorate. The results indicate that servant leadership significantly influences the creation of a risk culture but not internal audit effectiveness directly. However, auditor competence and risk culture significantly enhance internal audit effectiveness. Additionally, servant leadership indirectly improves internal audit effectiveness through the creation of a risk culture. The study highlights the need for fostering a risk culture and enhancing auditor competence to improve internal audit effectiveness in newly established institutions like BRIN.